Optimal INR level for warfarin therapy after mechanical mitral valve replacement - Itthidet Kamthornthanakarn (2020)
© 2019 The Author(s). Background: Data are scarce regarding the optimal international normalized ratio (INR) in Thai patients who require warfarin therapy after mechanical mitral valve replacement. Accordingly, the aim of this study was to identify the optimal INR level for warfarin therapy after mechanical mitral valve replacement in Thai patients. Methods: This is a retrospective cohort study design. We retrospectively reviewed the medical records of mechanical mitral valve replacement patients who received warfarin therapy at Siriraj Hospital. INR range was classified into 6 groups (< 2, 2.0-2.4, 2.5-2.9, 3.0-3.4, 3.5-4.5, and > 4.5). The optimal INR level was defined as the level with the lowest incidence density of thromboembolic or hemorrhagic complications. Results: Two hundred patients were included and followed over a period of 707.81 patient-years. Mean duration of follow-up was 3.53 ± 1.27 years. Eleven patients experienced 13 thromboembolic events (3.42 per 100 patient-years), and 12 patients experienced 18 total bleeding events (5.50 per 100 patient-years). Intracranial bleeding occurred in 3 patients (2.62 per 100 patient-years). The percentage of patient time spent within INR 2.5-3.4, INR < 2.5, and INR > 3.4 was 41.96, 54.04, and 4%, respectively. The overall event rate was lowest in the 2.0 to 3.4 INR range. Statistically significant differences were observed between INR 2.3 to 4 and < 2 (p < 0.001) and between INR 2.3 to 4 and > 3.4 (p < 0.001). Conclusions: The optimal INR level was within the range of 2.0 to 3.4 in our cohort of Thai mechanical mitral valve replacement patients.